2019
DOI: 10.22146/jcoemph.47513
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of interprofessional education in community setting

Abstract: Community health problem(s) needs to be solved collaboratively among the health care team. Interprofessional Education (IPE) is implemented to facilitate health students to collaborate before they join in the working world. The purpose of this study was to identify the experience of students, lecturers, and family members in the implementation of IPE in a community setting. All (465) sixth semester medical, nursing, and nutrition students in the Faculty of Medicine Universitas Diponegoro participated in the IP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 23 publications
(29 reference statements)
0
4
0
1
Order By: Relevance
“…The result of this study is in line with previous research, which conducted the IPE programme in normal conditions and reported that participating in the IPE programme made students appreciate and respect other health professionals' roles and scope (Ntsiea et al, 2021). In addition, when implemented in the community setting, IPE facilitates students to learn how to solve community health problems collaboratively (Asmara et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The result of this study is in line with previous research, which conducted the IPE programme in normal conditions and reported that participating in the IPE programme made students appreciate and respect other health professionals' roles and scope (Ntsiea et al, 2021). In addition, when implemented in the community setting, IPE facilitates students to learn how to solve community health problems collaboratively (Asmara et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Sesuai tinjauan aspek proseptual dan intelektual tersebut, dikemukakan bahwa perbedaan individu dapat di ungkapkan oleh tipe-tipe kognitif yang di kenal dengan gaya kognitif (cognitive style) (Safrida et al, 2015) Menurut Bestiyana (2018), bahwa gaya kognitif merupakan kebiasaan seseorang dalam memperoses informasi. Gaya kognitif adalah karakteristik individu dalam pengunaan fungsi kognitif (berfikir, mengingat, memecahkan masalah, membuat keputusan, mengorganisasi, dan memproses informasi dan seterusnya) yang bersifat konsisten dan berlangsung lama (Asmara et al, 2019). Jadi, Gaya kognitif merupakan ciri individu dalam berpikir, merasakan, mengingat, memecahkan masalah dan membuat keputusan.…”
Section: Pendahuluanunclassified
“…Lack of students' preparedness to interact with the community might cause varying degrees of community engagement between groups. 15 To reduce the gap, before community placement, students should be provided with an introductory course on how to engage the community. The course discusses local culture, social structure, and social skills.…”
Section: Interprofessional Learning Is Driven By Community Engagementmentioning
confidence: 99%